Arransemen Lagu Anak Sekolah - Natasha Amalia Putri; Harisnal Hadi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
School children's songs are Indonesian pop songs created by Oddie Agam which contain love stories during school. The aim of this work is to create a work in the form of school music. In this work, the arranger works on school children's songs in the form of school music and then combines them with a touch of drumband to form a new arrangement to be performed. The nuance of the arrangement will be packaged cheerfully and cheerfully. This